EDUKASI MASYARAKAT MANDIRI DESA SIAGA ANTI DIABETES - AHDIAH IMROATUL MUFLIHAH; Rian Anggia Destiawan (LPPM Universitas dr. Soebandi, 2025)
Diabetes mellitus is a disease or metabolic disorder characterized by increased sugar levels and accompanied by impaired metabolism of carbohydrates, lipids, and proteins. Common problems in the community are diabetes and hypertension. Diabetes can be prevented by eating a healthy diet and controlling blood sugar levels. One way to control blood sugar levels is to measure blood sugar levels using a tool, but the problem is that many people cannot use the tool. The community service aims to implement a community-based education program that facilitates the community in increasing knowledge about early detection and self-examination of Diabetes Mellitus. Methods In this study, diabetes mellitus education and demonstration of tools for detecting blood sugar levels. The results are community support to reduce diabetes levels by exercising, getting enough rest, and regularly checking blood sugar. The conclusion is that the community after education understands how to control blood sugar levels and conduct independent examinations.